Effect of pressure and excitation power on up-conversion assisted white light emission in yttrium oxide and silicate nanophosphors - (:unkn) unknown (TechConnect, 2016)
The production of warm artificial white light (WL) become a big challenge of engineers and scientists after the revolutionary introduction of incandescent lamp by Thomas Edison. Although several strategies have been developed in past, none of them was able to reach color quality of incandescent lamp because all these technologies suffer from low Color Rendering Indexes (CRI) and/or high Correlated Color Temperatures (CCT) which are not suitable for human perception. Recently, we were able to produce white light emission from un-doped and REIs doped Yttrium Oxide and Silicates with color quality parameters comparable with those of an incandescent lamp induced by infrared laser diode excitation. The characteristics of the white light emission both from yttrium oxide and silicate and the physical parameters that affect the white light emission were determined. A detailed comparison of the white light emission from yttrium oxide and yttrium silicate were made. The role of the type and the amount of the dopant ions on the production of the white light emission were determined.
Keywords: Absorption; Emission; Nanophosphor; White light; XRD